5. The Innovative Praxeology: Suggestions for Implementing in Artistic Education - Bularga Tatiana (Sciendo, 2020)
The process of artistic perception in instructive and formative actions is identified with the educative action itself. In this process the considerable weight rests on the participative state kid to the design, development and evaluation/self-evaluation (through prescription of individual behavioural maps, anticipating practical actions, varying operations, performing the tasks by choosing the optimal variants for solving) and the dynamics of professional competence of teachers to achieve gradually the theoretical design process and practical actuating, by identifying educational content and valuable actions, diagnosing the individual resources, planning, forming hypotheses, sequential and final evaluation. In our statements we proceed from the reality that the artistic activity differs much from other human activities through its ontological specifics, which requires taking into account the opportunities and challenges that arise in individual potential manifestation of the child, act that expresses by transposing the theoretical prescriptions into practical actions indisputable by the presence of emotional-affective reactions, by developing projects and logistical maps of action, is not waiting for certain stimuli coming from outside, but by enhancing the artistic intentions and decisions of child - subjects of education.